The influence of concomitant pathology on the course of pyelonephritis in combatants - O.S. Kolisnyk; Т.А. Bibik; O.Ya. Antonyuk (Počki)
Background. Pyelonephritis (PN) is an infectious inflammatory disease of the renal interstitium caused by nonspecific bacterial flora. PN leads to the formation of focal nephrosclerosis and is characterised by a high risk of recurrence, causing chronic kidney disease (CKD) in some cases. In 2017, 697.5 million cases of CKD were registered in the world, corresponding to an age-standardised prevalence of 8,724 per 100,000 population, and CKD caused 1.2 million deaths. During this period, 7.8 million cases of CKD were registered in Ukraine (the age-standardised prevalence was 11,571 per 100,000 population). The purpose was to analyse the relationship between the presence of comorbid pathology and the duration of inpatient treatment шт combatants with PN. Materials and methods. We analysed PN course in military personnel treated in the Nephrology Clinic of the National Military Medical Clinical Center “Main Military Clinical Hospital” from 2021 to 2023. The primary sources of information were the medical records of military personnel (form 2), the medical card of an inpatient (form 003/o), and the record book of patients in the clinic. We used the Charlson index to assess comorbidity. Diseases of service members were diagnosed following IСD-10. We used Excel and Statistica 12 programs for data processing. Results. The average age of participants was 44.23 ± 10.12 years. Comorbid pathology was observed in 102 (86.44 %) of 118 patients. It was found that the most common comorbidities among those used to calculate the Charlson comorbidity index in combatants with PN were diseases of the circulatory system — 47.46 % (2.31 ± 0.65 points), digestive organs — 11.86 % (1.83 ± 0.69 points), endocrine system — 9.32 % (2.41 ± 0.67 points), respiratory organs — 6.78 % (1.16 ± 0.39 points), musculoskeletal system — 4.2 % (1.50 ± 0.40 points), other classes of diseases — 6.8 % (1.40 ± 0.51 points). In total, according to the main classes of diseases, the average Charlson comorbidity index was 1.97 ± 0.42 points (n = 102). The presented results make it possible to assess the influence of concomitant pathology on the course and duration of treatment in service members with PN in hospital conditions by main classes of diseases. Conclusions. We have found that the most common comorbidities among service members with PN were diseases of the circulatory system — 47.46 %, digestive organs — 11.86 %, endocrine system — 9.32 %, and diseases of the respiratory organs — 6.78 %. It has been proven that age affects the length of stay in the hospital (χ2 = 34.93; df = 9; p < 0.001). In turn, with age increase, comorbidities and bed-days increase. Using the Spearman and Kendall rank correlation coefficient, a relationship was found between the duration of treatment in a hospital and the presence of concomitant pathology in patients, which proves an increase in the number of days of hospital stay in patients with multimorbidity (r = 0.7344; р < 0.001; n = 118). Given the high risks of complications in PN, timely referral of patients to a specialised inpatient department is essential. Treatment should be based on the principles of evidence-based medicine and involve a personalised approach to risk assessment in order to prevent complications.